Germline variation in inflammation-related pathways and risk of Barrett’s esophagus and esophageal adenocarcinoma - Buas, M; He, Q; Johnson, L; Palles, C; Love, S; Tomlinson, I (BMJ Publishing Group, 2016)
Objective: Esophageal adenocarcinoma (EA) incidence has risen sharply in Western countries over recent decades. Local and systemic inflammation is considered an important contributor to EA pathogenesis. Established risk factors for EA and its precursor, Barrett’s esophagus (BE), include symptomatic reflux, obesity, and smoking. The role of inherited genetic susceptibility remains an area of active investigation. Here, we explore whether germline variation related to inflammatory processes influences susceptibility to BE/EA. Design: We used data from a genome-wide association study (GWAS) of 2,515 EA cases, 3,295 BE cases, and 3,207 controls. Our analysis included 7,863 single nucleotide polymorphisms (SNPs) in 449 genes assigned to five pathways: cyclooxygenase (COX), cytokine signaling, oxidative stress, human leukocyte antigen, and NFB. A principal components-based analytic framework was employed to evaluate pathway-level and gene-level associations with disease risk. Results: We identified a significant signal for the COX pathway in relation to BE risk (P=0.0059, FDR q=0.03), and in gene-level analyses found an association with MGST1 (microsomal glutathione-S-transferase 1; P=0.0005, q=0.005). Assessment of 36 MGST1 SNPs identified 14 variants associated with elevated BE risk (q<0.05). Four of these were subsequently confirmed (P<5.5 × 10-5) in a meta-analysis encompassing an independent set of 1,851 BE cases and 3,496 controls, and are known strong eQTLs for MGST1. Three such variants were associated with similar elevations in EA risk. Conclusion: This study provides the most comprehensive evaluation of inflammation-related germline variation in relation to risk of BE/EA, and suggests that variants in MGST1 influence disease susceptibility.